Organic and inorganic nanoparticle vaccines for prevention of infectious diseases. (3rd April 2020) - Poon, Christopher; Patel, Amish A
Abstract: Infectious diseases remain a leading cause of concern worldwide. Conventional vaccine methods to elicit immune responses have limitations in effectively controlling new and re-merging pathogens. Nanoparticle-based vaccines show promise in overcoming these limitations due to their versatility and tunability to protect antigen from premature degradations, facilitate their intracellular uptakes and elicit prolonged immunity against infectious diseases. Nanoparticle can be categorized as purely organic or inorganic based on the components that construct the structure. Most organic materials are biocompatible, biodegradable, and nontoxic, while most inorganic materials have a smaller particle size, improved stability, controlled tunability, enhanced permeability, high antigen loadings, and a triggered release profile. This review will focus on the different type of organic and inorganic nanoparticles used as vaccine against infectious diseases.